Progress in structural studies of proteins by NMR spectroscopy - Kazimierczuk, K.; Misiak, M.; Zawadzka, A.; Koźmiński, W. (Polimery, 2022)
In this review we discuss recent advances in the field of NMR structural studies of proteins. We mention the development of new spectrometer hardware, novel experimental techniques and sample preparation. The approaches improving obtained structures, like analysis of Residual Dipolar Couplings, and enabling studies of large molecules as for example TROSY and CRINEPT are compared. As the most important, achievements in the field of fast multidimensional NMR are discussed in details.